2020
DOI: 10.1038/s41598-020-68827-0
|View full text |Cite
|
Sign up to set email alerts
|

Tall fescue sward structure affects the grazing process of sheep

Abstract: The study of factors influencing animal intake can provide a better understanding of the dynamics of the pasture ecosystem and serve as a basis for managing livestock in a more efficient way. We measured different sward surface heights of tall fescue in the process of short-term intake rate of sheep. There was a significant effect of sward surface height on herbage mass ( P < 0.001), leaf lamina mass ( P < 0.001), other species mass ( P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…It is based on the optimal foraging theory that states maximization of the intake rate of energy over the grazing process through decisions within different space-time scales (Charnov 1976;Pyke et al 1977). The results of Szymczak et al (2020b) agreed with studies that demonstrated intermediate SSH at the STIR − max for other forage species (Fonseca et al 2012;Mezzalira et al 2014;Silva et al 2017). These nding have implications at the plant-animal interface.…”
Section: Animal Intakesupporting
confidence: 66%
See 4 more Smart Citations
“…It is based on the optimal foraging theory that states maximization of the intake rate of energy over the grazing process through decisions within different space-time scales (Charnov 1976;Pyke et al 1977). The results of Szymczak et al (2020b) agreed with studies that demonstrated intermediate SSH at the STIR − max for other forage species (Fonseca et al 2012;Mezzalira et al 2014;Silva et al 2017). These nding have implications at the plant-animal interface.…”
Section: Animal Intakesupporting
confidence: 66%
“…A study conducted by Szymczak et al (2020b) in the same experimental area as this one (same area, experimental and climate conditions and forage species), demonstrated a signi cant effect of tall fescue SSH on STIR of sheep. There was a quadratic response of STIR to SSH, increasing up to a SSH of 22.3 cm (y = 5.61 g DM min − 1 ) and decreasing at taller SSH (Fig.…”
Section: Animal Intakementioning
confidence: 80%
See 3 more Smart Citations